ANALISIS KETERSEDIAAN DAN KEBUTUHAN AIR BAKU DISTRIK BONGGO KABUPATEN SARMI - Diane Merani, Marice; Mujiati; Manalu, Janviter (Jurnal ELIPS (Ekonomi, Lingkungan, Infrastruktur, Pengembangan Wilayah, dan Sosial Budaya), 2024)
The development of an area will cause the demand for water to continue to increase along with the population growth rate. The fulfillment of food needs and the activities of the population are always closely related to the need for water. The demands are unavoidable but must be predicted and planned for optimal utilization. The tendency that often occurs is the imbalance between water availability and water demand. To achieve a balance between water demand and availability in the future, efforts are needed to assess the components of raw water availability and demand as clean water sources. The source of clean water for the people of Bonggo District, Sarmi Regency, comes from borehole pumps, shallow wells (pumps), and rainwater. The analysis results on the need for domestic and non-domestic clean water in the Bonggo District in 2023 show a total requirement of 210.38 liters/day or 0.0024 m3/second. The need for clean water is expected to increase by 2043, with the total requirement for domestic and non-domestic clean water reaching 285,820 liters/day or 0.0033 m3/second. The availability and need for clean water sourced from raw water that can be utilized as clean water comes from pump bore wells as a suitable raw water source. In terms of quantity, it is available 24 hours a day and throughout the year. The investigation results of the pump bore well raw water source meet the clean water quality requirements according to Government Regulation No. 82 of 2001, Level II. This is supported by groundwater, obtained through the analysis of geological conditions, land cover, morphology, and river flow, which have a high to very high groundwater potential score, located in the northern part of Bonggo District. Economically, in terms of quantity, rainwater can be used as clean water due to its sufficient availability, with high rainfall (104,775 mm/year) and year-round service (continuity), and in terms of quality, the results of rainwater quality tests meet the clean water standards according to quality standards.